Business and Human Development in the Base of the Pyramid: Exploring Challenges and Opportunities with Market Heat Maps - Acosta, Pablo; Kim, Namsuk; Melzer, Illana; Mendoza, Ronald U.; Thelen, Nina (2012)
Roughly a little under half of the world's population is mired in poverty, most in the developing world--about 3 billion people constitute the global base of the economic pyramid. Building on earlier work by Banerjee and Duflo (2007), this paper uses survey data from three countries in order to provide a clear visualization of the spatial dimension of the economic lives of the poor and their access to markets. It develops a framework that could be used to map market inclusiveness, and then applies this to a number of markets that are critical to reducing poverty and increasing human welfare: water, credit and telecommunications. These "market heat maps" help to illustrate the extent of the challenges and in some cases reveal potential opportunities in growing more inclusive markets for the poor.